Evaluation of confirmatory data following the Article 12 MRL review and modification of the existing maximum residue levels for deltamethrin in tomatoes and okra/lady's fingers. (14th March 2022) - ,; Bellisai, Giulia; Bernasconi, Giovanni; Brancato, Alba; Cabrera, Luis Carrasco; Ferreira, Lucien; Giner, German; Greco, Luna; Jarrah, Samira; Leuschner, Renata; Magrans, Jose Oriol; Miron, Ileana; et al.
Abstract: The applicants Bayer SAS – Crop Science Division, Diachem S.p.A. and Isagro S.p.A., submitted two requests to the competent national authority in Austria to evaluate the confirmatory data identified for deltamethrin in the framework of the maximum residue level (MRL) review under Article 12 of Regulation (EC) No 396/2005 as not available. The application from Bayer SAS – Crop Science Division also included a proposal for the modification of the MRL for deltamethrin in tomatoes in accordance with Article 6 of Regulation (EC) No 396/2005. A third application was submitted by the Federal Public Service (FPS) Health, Food chain safety and Environment on behalf of Belgium, to modify the existing maximum residue level for the active substance in okra/lady's fingers. The three applications were combined by EFSA under the current assessment. The data gaps based on monitoring analytical methods were addressed; the data gaps on storage stability studies, processing trials in potatoes, metabolism studies of deltamethrin isomers in livestock and livestock feeding studies were not addressed by providing the requested experimental data; data gap on residue trials analysing simultaneously for monitoring and risk assessment residue definitions was not addressed for most of the concerned crops and requires risk managers' decisions in numerous cases. The new information provided requires a revision of certain existing MRLs. Adequate analytical methods for enforcement are available to control the residues of deltamethrin in plant and animal matrices at the validated limit of quantification (LOQ) of 0.01 mg/kg. Based on the results of the refined risk assessment following evaluation of the confirmatory data, EFSA concluded that the short‐term and long‐term intake of residues resulting from the proposed uses of deltamethrin according to the reported agricultural practices are unlikely to present a risk to consumer health. The risk assessment shall be regarded as indicative and affected by non‐standard uncertainties.